REKONSEPTUALISASI PENGATURAN RESTITUSI DAN KOMPENSASI KEPADA KORBAN TINDAK PIDANA INVESTASI ILEGAL SKEMA PONZI DIKAITKAN DENGAN UPAYA PERLINDUNGAN HUKUM DI INDONESIA - Sayladito Sitinjak; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In general, the Indonesian population is still largely unfamiliar withvarious new instruments in the world of investment. In fact, some members of thesociety seem uninterested in learning how to invest wisely and correctly. Often,people are focused on the potential returns they can gain, so the first question thatarises when a new investment opportunity is presented is about the expectedprofits. Some individuals appear to be dazzled by the promise of high profitswithout considering the accompanying risks. Consequently, the phenomenon ofinvestment scams or fraudulent investments has emerged. It appears as if aninstitution is managing the public's funds and investing them in various types ofinvestments, but in reality, it's merely a money game.This research is a normative legal study based on literature research,which involves quoting from relevant books or supporting materials related to theissues under investigation. The research utilizes secondary data sources,including primary, secondary, and tertiary legal materials. This study alsoemploys qualitative data analysis and produces descriptive data.From the research findings and discussions conducted, it can beconcluded that the regulation of restitution and compensation for victims ofillegal investment schemes, particularly Ponzi schemes, concerning legalprotection efforts in Indonesia, is not effectively implemented. This is due to theperception that law enforcement against perpetrators is lenient and relies solelyon the Criminal Code penal Indonesia. Different regulations naturally servedifferent purposes and objectives to ensure that the rules can be appliedaccording to the actions of the criminals. Many cases involve victims of criminalactivities who do not receive restitution to recover their losses, both material andimmaterial. Criminal justice has not provided certainty regarding the fulfillmentof restitution.Keywords: Ponzi schemes-investment-restitution-legal protection.